2019
DOI: 10.26444/aaem/99233
|View full text |Cite
|
Sign up to set email alerts
|

Increasing deaths from colorectal cancer in Poland – Insights for optimising colorectal cancer screening in society and space

Abstract: Introduction and objective.With respect to the increasing numbers of deaths due to colorectal cancer in Poland, the aim of the study was to investigate socio-demographic characteristics which influence colorectal cancer screening acceptance and to assess spatial variation of colorectal cancer mortality. Materials and method. An age-period-cohort model was estimated to assess mortality trends in colorectal cancer in Poland. A geographical analysis was performed by spatial regression. Factors influencing partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
4
0
2
Order By: Relevance
“…Using the search term 'processed red meat and cancer' in PubMed, it is clear that there has been a systematically increasing annual number of publications focused on this topic, especially after 2015: only one in 1990, near to 50 each year 2010‐2015 and about 80 each year 2016‐2020. Most of them agree to a greater or lesser extent – that the consumption of red and processed meat is associated with an increased risk of cancer, especially colorectal cancer (Abu‐Ghazaleh et al ., 2021; Aykan, 2015; Behrens et al ., 2018; Czaderny, 2019; Ganjavi & Faraji, 2019; Knuppel et al ., 2020; Mafiana et al ., 2018; Pouchieu et al ., 2014; WCRF/AICR, 2018; Saliba et al ., 2019). In contrast, only a few studies have not reached the same conclusion (Pramual et al ., 2018).…”
Section: Cancer Cvd Type‐2 Diabetes and Total Mortalitymentioning
confidence: 99%
“…Using the search term 'processed red meat and cancer' in PubMed, it is clear that there has been a systematically increasing annual number of publications focused on this topic, especially after 2015: only one in 1990, near to 50 each year 2010‐2015 and about 80 each year 2016‐2020. Most of them agree to a greater or lesser extent – that the consumption of red and processed meat is associated with an increased risk of cancer, especially colorectal cancer (Abu‐Ghazaleh et al ., 2021; Aykan, 2015; Behrens et al ., 2018; Czaderny, 2019; Ganjavi & Faraji, 2019; Knuppel et al ., 2020; Mafiana et al ., 2018; Pouchieu et al ., 2014; WCRF/AICR, 2018; Saliba et al ., 2019). In contrast, only a few studies have not reached the same conclusion (Pramual et al ., 2018).…”
Section: Cancer Cvd Type‐2 Diabetes and Total Mortalitymentioning
confidence: 99%
“…The areas with high incidence of DTC (such as liver, gastric, and esophageal cancer) exhibited obvious regional differences, indicating that they were greatly affected by environmental factors. Many studies con rmed that there is a signi cant relationship between the ecological environment, population behavior, and the incidence of cancer [29][30][31] . During the eld investigation, it was found that the amount of pesticides and fertilizers used in the northwestern region in Lujiang County was signi cantly higher than the other regions(Fig.…”
Section: Spatiotemporal Clustering Of Digestive Tract Cancermentioning
confidence: 99%
“…Badanie było realizowane techniką wywiadu wspomaganego komputerowo albo ankiety wypełnianej samodzielnie przez respondenta oraz uzupełniająco techniką ankiety internetowej. Statystyczne modele przestrzenne umieralności na nowotwory złośliwe jelita grubego oraz płuca w Polsce przedstawił Czaderny (2019aCzaderny ( , 2019b.…”
Section: Metody Klasteryzacjiunclassified
“…Na mapach zilustrowano dane o umieralności za lata 2010-2014 oraz referencyjnie 1980-1984, otrzymane z Krajowego rejestru Nowotworów, pochodzące ze świadectw zgonów gromadzonych przez Główny Urząd Statystyczny. Czaderny (2019aCzaderny ( , 2019bCzaderny ( , 2018 omówił rozkład przestrzenny umieralności na nowotwory złośliwe jelita grubego, płuca oraz gruczołu krokowego w Polsce. W niniejszym artykule zanalizowano zróżnicowanie przestrzenne rejestrowanej umieralności na inne ważne nowotwory złośliwe: tarczycy (iCD10: C73; iCD9: 193), żołądka (C16; 151), pęcherza moczowego (C67; 188), jądra (C62; 186), jajnika (C56; 183), sutka u kobiet (C50; 174) oraz macicy (C53-C54; 180, 182).…”
unclassified